Damping properties of a beam with vacuum-packed granular damper. (14th April 2015) - Bajkowski, Jacek Mateusz; Dyniewicz, Bartłomiej; Bajer, Czesław I.
Abstract: An experimental study of the properties of a layered beam partially treated with a damping element based on a granular material is presented. The beam structure comprises two aluminium face strips connected at the tip by a hermetic, elastic envelope, filled with bulk granules. Changing the underpressure value inside the airtight envelope allows variation of the mechanical properties of such a complex system, like stiffness or damping coefficients. Four types of granules, different in size, shape, and material, were examined to find the most promising one. A detailed discussion of the experimental amplitude, frequency, and damping capacity of the cantilever is given. The Zener, Kelvin–Voigt, and classic Maxwell models were employed for modelling and parameter identification. The range of applicability and limitations of the proposed solution has been given, as well as the benefits from the application. Abstract : Highlights: Damping element based on a granular material is presented. Sandwich beam with two aluminium face strips connected at the tip by a hermetic envelope, filled with bulk granules. Changing the under pressure value enables varying the mechanical properties. Experiment proves that the material is efficient in semi-active damping of vibrations.